Integrasi Teknologi dalam Pembelajaran Matematika: Belajar dari SAMR dan MAAAD - Muhammad Taqiyuddin; Faliqul Jannah Firdausi; Mohamad Tri Afriyadi Nur Asidin (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2021)
We are now facing a growing demand of using technology in mathematics classrooms due to the unprecedented Covid-19 pandemics era. In this situation, most teachers among the globe including Indonesia have to employ remote learning practice without proper training and sufficient experience in doing so. This article aims to provide teachers and mathematics education communities, especially in Indonesia, with some research-based principles mainly from SAMR and MAAAD frameworks on how they productively incorporate technology in their mathematical teaching and learning. By doing so, we explain how we can improve our technology integration and how we analyse technology affordances. In addition, we also raise the importance of acknowledging technology limitations, along with the discussion on what to do next for improving our technology integration skills. Keywords: MAAAD, Mathematics Education, SAMR, Technology Integration.